2007
DOI: 10.5488/cmp.10.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Towards an analytical theory for charged hard spheres

Abstract: Ion mixtures require an exclusion core to avoid collapse. The Debye Hueckel (DH) theory, where ions are point charges, is accurate only in the limit of infinite dilution. The mean spherical approximation (MSA) is the embedding of hard cores into DH, and is valid for higher densities. The properties of any ionic mixture can be represented by the single screening parameter Γ which for the equal ionic size restricted model is obtained from the Debye parameter κ. This Γ representation, the binding mean spherical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…15,16 The MSA calculations were examined vis à vis the Monte Carlo ͑MC͒ data in Broccio et al 15 It was found that the MSA according to Blum and Hoye 4 performed reasonably well at weak attraction ͑K 1 Ͻ 2.5͒, but deteriorated for strong attraction ͑K 1 Ͼ 2.5͒, while the hypernettedchain ͑HNC͒ equation 18 gave more accurate structure factors S͑q͒ over the whole range of K 1 studied. It is conceivable that the more modern versions of MSA as given by Blum and Arias 19,20 for the n-Yukawa potentials will also give good results. Broccio et al 15 in 2006 presented a very thorough IE study.…”
Section: Introductionmentioning
confidence: 94%
“…15,16 The MSA calculations were examined vis à vis the Monte Carlo ͑MC͒ data in Broccio et al 15 It was found that the MSA according to Blum and Hoye 4 performed reasonably well at weak attraction ͑K 1 Ͻ 2.5͒, but deteriorated for strong attraction ͑K 1 Ͼ 2.5͒, while the hypernettedchain ͑HNC͒ equation 18 gave more accurate structure factors S͑q͒ over the whole range of K 1 studied. It is conceivable that the more modern versions of MSA as given by Blum and Arias 19,20 for the n-Yukawa potentials will also give good results. Broccio et al 15 in 2006 presented a very thorough IE study.…”
Section: Introductionmentioning
confidence: 94%